The prince and the pauper - Twain, Mark, 1835-1910. (New York : Bantam, 1991)
When young Edward VI of England and a poor boy who resembles him exchange places, each learns something about the other's very different station in life.
Includes bibliographical references (p. 218).
Young Adult
Young Adult.
1160
Keywords: Edward -- VI, -- King of England, -- 1537-1553 -- Fiction; Impostors and imposture -- England -- Fiction; Princes -- England -- Fiction; Poor -- England -- Fiction; Boys -- England -- Fiction; Edward -- VI, -- King of England, -- 1537-1553 -- Fiction; Impostors and imposture -- Fiction; Princes -- England -- Fiction; Poor -- England -- Fiction; Boys -- Fiction; Historical fiction; Historical fiction